2018
DOI: 10.1186/s12967-018-1679-0
|View full text |Cite
|
Sign up to set email alerts
|

Significance of intrinsic breast cancer subtypes on the long-term prognosis after neoadjuvant chemotherapy

Abstract: BackgroundThe prognosis of breast cancer and the treatment response to neoadjuvant chemotherapy (NAC) differ depending on the intrinsic molecular subtypes. We evaluated the prognostic significance of immunohistological subtypes in patients with recurrent breast cancer after treatment with NAC and surgery.MethodsA total of 237 patients with breast cancer treated with NAC and subsequent curative surgery between 2007 and 2015 were analyzed. The correlation between intrinsic molecular subtypes and clinicopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
(28 reference statements)
0
15
2
3
Order By: Relevance
“…Classification of intrinsic subclasses is helpful in the prediction of therapeutic response and prognosis of BrCa [19]. So, we next compared the differential transcriptional levels of PRDX family members according to different intrinsic subclasses of BrCa.…”
Section: Resultsmentioning
confidence: 99%
“…Classification of intrinsic subclasses is helpful in the prediction of therapeutic response and prognosis of BrCa [19]. So, we next compared the differential transcriptional levels of PRDX family members according to different intrinsic subclasses of BrCa.…”
Section: Resultsmentioning
confidence: 99%
“…Neoadjuvant chemotherapy (NAC) is currently widely used in patients with locally advanced breast cancer to transform nonoperable cases into operable ones, thus improving breast preservation rates and reflecting the sensitivity of tumour cells to systemic therapy [ 1 3 ]. A large number of studies have shown that postmastectomy radiotherapy (PMRT) can significantly reduce the locoregional recurrence rate (LRR) of patients with stage II-III breast cancer and increase overall survival (OS) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…ER-positive tumors are further subtyped into low proliferation rate luminal A and higher proliferation rate luminal B tumors. Patients with the triple negative breast cancer (TNBC) subtype, characterized by the absence of ER, progesterone receptor (PR), and human epidermal growth factor receptor-2/neu receptors (HER2/neu) have a poor prognosis [5,6] also due to the few clinical treatments available. Considerable effort has gone into identifying new therapeutic agents, with multiple targeting abilities, able to circumvent the limitation of current conventional therapy.…”
Section: Introductionmentioning
confidence: 99%